Uppdatering av båtnadskalkyl med hänsyn till nya faktorer - Stoor, Martin (2008)
Sweden have 419 000 km road in the country and about half of these roads is forestroads. The forest road net most important mission is to make it possible to deliver wood from the forest to the industries. With a raw material that is spread over a large area the road network is important. Each year has the forest road network been extended with about 1 700 km new roads. To decide if a new road is to be built different forest road cost estimation models has been used.